Epigenetics and psychiatric disease - Grayson, Dennis Robert, 1953- (Progress in molecular biology and translational science ;, 2018)
Epigenetics and Psychiatric Disease, Volume 157, the latest volume in the Progress in Molecular Biology and Translational Science series, includes recent developments on a variety of topics, including the Epigenetic landscapes of the adversity-exposed brain, Chromosomal conformations and epigenomic regulation in schizophrenia, Progress in the epigenetics of depression, the epigenetics of circadian rhythms in imprinted neurodevelopmental disorders, DNA methylation mediating substance abuse, mechanisms and therapeutic opportunities, DNA methylation in animals model of psychosis, Epigenetics of early life stress, Epigenetic drugs for mood disorders, and more. Accessible to students and researchers alike, with content that appeals to a variety of readersWritten by leading authorities in their respective fields of molecular biology.